Broadening the temperature range for high thermoelectric performance of bulk polycrystalline strontium titanate by controlling the electronic transport properties. Issue 28 (5th July 2018) - Li, Jian-Bo; Wang, Jun; Li, Jing-Feng; Li, Yan; Yang, He; Yu, Hao-Yang; Ma, Xiao-Bo; Yaer, Xinba; Liu, Liang; Miao, Lei
Abstract : Strontium titanate (SrTiO3 ) is a promising n-type thermoelectric material at high temperature. Abstract : Strontium titanate (SrTiO3 ) is a promising n-type thermoelectric material at high temperature. However, to date, its reported high dimensional figure of merit ( zT ) > 0.4 has only been achieved in a narrow temperature range near 1000 K. In this study, zT values of >0.4 were achieved in the broad temperature range of 769–1009 K in bulk SrTiO3 co-doped with La and Nb with in situ precipitation of second phases of NbC and TiO2− δ . The electronic transport properties of the samples were optimized by adjusting the doping ratio, resulting in a large power factor of 1.82 mW m −1 K −2 at 622 K for 7 mol% La–7 mol% Nb-doped SrTiO3 . Notably, the power factor (PF) decreased more gradually with increasing temperature, resulting in a high PF of 1.28 mW m −1 K −2 even at 1009 K. In addition, precipitation of the second phases occurred during sintering of the mixture of La–Nb doped SrTiO3 nano powder and carbon powder, which provided additional phonon scattering centers except for the phonon scattering centers of La and Nb point defects. This high thermoelectric performance achieved over a broad temperature range could be beneficial for broadening the range of application temperatures for bulk polycrystalline SrTiO3 . Furthermore, the tailoring strategy of co-doping, an in situ second phase, and oxygen vacancies applied in this study may be applicable to other oxide thermoelectric materials.